POTENSI ENZIM SELULASE DARI BAKTERI TERMOFILIK DI KAWASAN WISATA IE SUUM KABUPATEN ACEH BESAR - Rahmatil Majidah; Syafrina Sari Lubis; Diannita Harahap (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2023)
Thermophilic bacteria are a group of bacteria that grow at a temperature range of 45oC to 80oC and have the potential to produce cellulase enzymes. The tourist area of Ie Suum, Aceh Besar District is one of the hot springs in Aceh. This study aims to observe the morphological characteristics, cellulase enzyme potential and activity test in producing cellulase enzymes from thermophilic bacteria found in Ie Suum. The method of isolating thermophilic bacteria uses the pour plate method and testing the cellulase enzyme activity using the DNS (3,5-dinitrosalicylic Acid) method. 15 isolates were obtained, namely 13 Gram positive and 2 Gram negative, 2 genera were obtained, namely the genus Bacillus sp. and the genus Pseudomonas sp. Based on the potential of the cellulase enzyme, the 15 isolates showed the largest clear zone diameter, namely isolate TS6 3,67 cm, isolate TS7 2,33 cm, and isolate TS10 4,00 cm. The results of measuring enzyme activity using the DNS method obtained isolates TS6 4,7 x 10-3 U/mL, isolates TS7 4,4 x 10-3 U/mL, and isolates TS10 5,5 x 10-3 U/mL.